Polyethylene glycol aerobic biodegradability - Otal,E; Lebrato,J; Livingston,AG (Tecnologia Del Agua, 2001)
Polyethylebe glycol aerobic biodegradability. Biodegradability of polyethylene glycols of different molecular weight was assesed, due to the recalcitrant natures of these polymeric compounds, produced in many industrial wastewaters, hardly biodegradable. Using discontinuous cultures, inoculated whith and adapted inoculum for polyethylene glycols 10.000 for more than two years, the range from polyethylene glycols 200 to 10.000 could be eliminated. It has been found that biomess adapts to polymers of lower molecular weight, but is insufficient for those of greater weight.